OPTIMALISASI KREATIVITAS DAN PEMIKIRAN KRITIS MELALUI PEMBELAJARAN BERBASIS PROYEK DI SEKOLAH DASAR - Eka Fatmahwati; Liftiah; Sri Sumartiningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Critical thinking and creativity are two essential 21st-century competencies that must be developed from the elementary school level. However, learning practices in many schools still tend to focus on academic outcomes and provide limited opportunities for students to experiment and innovate. This article aims to examine the role of Project-Based Learning (PjBL) in enhancing elementary school students’ creativity and critical thinking skills through a literature review approach. The study utilizes various national and international academic references published between 2015 and 2025 that are relevant to the theories, implementation, and empirical findings of PjBL. The analysis is conducted descriptively by reviewing and comparing previous studies based on key thematic areas. The results indicate that PjBL effectively creates a student-centered learning environment that promotes collaboration, inquiry, reflection, and contextual problem-solving skills, all of which contribute significantly to improving students’ creativity and critical thinking. Therefore, the application of PjBL aligns with the principles of 21st-century learning and supports the Merdeka Belajar (Freedom to Learn) policy, which emphasizes student independence and active learning. Future research is recommended to explore the effectiveness of technology-based and collaborative PjBL implementation within the context of elementary education.